Armando Petrucci. Escribir cartas, una historia milenaria. Buenos Aires: Ampersand, 2018, 260pp. - Ferroggiaro, Federico (Badebec, 2019)
Armando Petrucci. Escribir cartas, una historia milenaria. Buenos Aires: Ampersand, 2018, 260pp.